Porcine Reproductive and Respiratory Syndrome Virus Evades Antiviral Innate Immunity via MicroRNAs Regulation - Zhang, Xuan; Feng, Wen-Hai (Frontiers in Microbiology, 2021)
Porcine reproductive and respiratory syndrome (PRRS) is one of the most important diseases in pigs, leading to significant economic losses in swine industry worldwide. PRRS virus (PRRSV) is an enveloped positive single-stranded RNA virus, which mainly infects cells of monocyte/macrophage lineage. MicroRNAs (miRNAs) are small single-stranded non-coding RNAs involved in the regulation of gene expressions at the post-transcriptional levels. In this review, we summarize current progresses on how PRRSV utilizes miRNAs for immune evasions. PRRSV is able to dysregulate the expression of a variety of host miRNAs, which influence multiple innate immune related molecules and signaling pathways to help the virus evade the host innate immune response. In addition, PRRSV also could encode miRNAs. The targets of these miRNAs are predicted, and their targets relate to host genes involved in the immune response, suggesting that microRNAs are exploited by PRRSV to escape host anti-virus surveillance and help virus infection. Nevertheless, pitfalls still exist in current studies. Our increasing knowledge of the role of miRNAs in immune evasion will improve the understanding of PRRSV pathogenesis and help us develop new treatments for PRRSV associated diseases.